PERAN PEMANDU LOKAL DALAM MENINGKATKAN KEPUASAN WISATAWAN DI DESA PENGLIPURAN, BALI - Syah Fira Ayuningtyas; Eka Putri Nurmayasari; Mulya Nur Aini; Tanziila; Masetya Mukti (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2026)
Penglipuran Traditional Village, a cultural tourism icon in Bali, is widely recognized for its commitment to environmental cleanliness and the preservation of traditional values. This study aims to examine in depth the contribution of local guides in enhancing visitor satisfaction. A mixed method approach was employed, combining both quantitative and qualitative analyses. Data collection techniques included field observations and the distribution of questionnaires to 62 respondents. The findings indicate that aspects such as information delivery, service ethics, communication skills, and the creativity of local guides received predominantly positive responses. The majority of respondents rated these aspects as